Epigenetic effects of insecticides on early differentiation of mouse embryonic stem cells. (September 2021) - Wang, Wenlong; Ito, Tomohiro; Otsuka, Satoshi; Nansai, Hiroko; Abe, Kuniya; Nakao, Yoichi; Ohgane, Jun; Yoneda, Minoru; Sone, Hideko
Abstract: Increasing evidence indicates that many insecticides produce significant epigenetic changes during embryogenesis, leading to developmental toxicities. However, the effects of insecticides on DNA methylation status during early development have not been well studied. We developed a novel nuclear phenotypic approach using mouse embryonic stem cells harboring enhanced green fluorescent protein fused with methyl CpG-binding protein to evaluate global DNA methylation changes via high-content imaging analysis. Exposure to imidacloprid, carbaryl, and o, p '-DDT increased the fluorescent intensity of granules in the nuclei, indicating global DNA methylating effects. However, DNA methylation profiling in cell-cycle-related genes, such as Cdkn2a, Dapk1, Cdh1, Mlh1, Timp3, and Rarb, decreased in imidacloprid treatments, suggesting the potential influence of DNA methylation patterns on cell differentiation. We developed a rapid method for evaluating global DNA methylation and used this approach to show that insecticides pose risks of developmental toxicity through DNA methylation. Highlights: We developed a rapid approach using GFP-MBD1 for evaluating epigenetic activity. Imidacloprid, carbaryl and o, p '-DDT affected DNA methylation during development. Imidacloprid decreased DNA methylation in genes related to various cell processes.